Проблема сущности и функций политической воли - А. Г. Навасардян (ՀՀ ԳԱԱ հրատ.)
Քաղաքագիտության ամենաուշագրավ երևույթներից է քաղաքական կամքը: Ելնելով դրա վերաբերյալ ժամանակակից գիտության, նախ և առաջ հոգեբանության բնագավառում ընդունված տեսակետից` կարելի է եզրակացնել, որ «քաղաքական կամք» կոչված երևույթը դեռևս անհրաժեշտ խորությամբ ուսումնասիրված չէ: This article concerns one of the important problems of contemporary politology; namely, that of political will of subjects of political power, its principal functions in political life of contemporary societies. Proceeding from modern psychological conception of human will, the author proposes his conception of political will and its functions in the process of problem solving, purposeful activity aimed to reach his political purposes.
Keywords: Political Science; J Political Science